Pengaruh Penggunaan Media Game Edukasi Wordwall terhadap Hasil Belajar Siswa - Nurasila Rahman; Suhardiman; Muldyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study is a quasi-experimental design aimed at determining the effect of Wordwall Educational Games on the learning outcomes of eighth-grade students in Social Studies (IPS). The design of this study is a nonequivalent control group using a pretest and posttest. The sample consists of two classes, namely the experimental class using Wordwall media and the control class using conventional learning. The test instrument used has been shown to be valid and reliable. Data were collected through tests and analyzed with normality tests, homogeneity, and t-tests to test the hypothesis. The results showed that the average posttest score of the experimental class increased significantly compared to the control class, with a t count (4.665) > t table (1.680) and a significance of 0.000 < 0.05. IPS learning using Wordwall media is proven to be better than conventional learning in improving students' learning outcomes.